Liposomal Formulation of Turmerone-Rich Hexane Fractions from Curcuma longa Enhances Their Antileishmanial Activity - Ana Claudia F. Amaral (BioMed Research International, 2014)
Promastigote forms of Leishmania amazonensis were treated with different concentrations of two fractions of Curcuma longa cortex rich in turmerones and their respective liposomal formulations in order to evaluate growth inhibition and the minimal inhibitory concentration (MIC). In addition, cellular alterations of treated promastigotes were investigated under transmission and scanning electron microscopies. LipoRHIC and LipoRHIWC presented lower MIC, 5.5 and 12.5 μg/mL, when compared to nonencapsulated fractions (125 and 250 μg/mL), respectively, and to ar-turmerone (50 μg/mL). Parasite growth inhibition was demonstrated to be dose-dependent. Important morphological changes as rounded body and presence of several roles on plasmatic membrane could be seen on L. amazonensis promastigotes after treatment with subinhibitory concentration (2.75 μg/mL) of the most active LipoRHIC. In that sense, the hexane fraction from the turmeric cortex of Curcuma longa incorporated in liposomal formulation (LipoRHIC) could represent good strategy for the development of new antileishmanial agent.